RISK FACTORS OFBIRTH ASPHYXIA IN PKU MUHAMMADIYAH HOSPITAL, BANTUL - Eka Riana; Fitria Yulastini; Umi Khasanah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Infant mortality rate particularly in the perinatal period, is significantly high and become a health problem both globally and nationally. The first thousand days of life are the golden periods for a child's growth. Health surveillance before and during pregnancy as well as in the birth process largely determines the quality of the child that will be born. Among four regions in Yogyakarta, Bantul region has the second highest number of infant mortality with 126 cases. The leading cause of infant death in this region is asphyxia which reaching 29 cases. In PKU Muhammadiyah Hospital, Bantul there were 264 (23%) infants from 1131 live births who suffered from asphyxia in 2014. Aims: To determine the risk factors of birth asphyxia in PKU Muhammadiyah, Hospital Bantul in 2014. Methods: This was an analytical observasional study, with case control study design. The study was conducted in PKU Muhammadiyah Hospital, Bantul. Samples were newborns in PKU Muhammadiyah Hospital, Bantul from January to December 2014. There were 167 respondents in case group and 167 respondents in control group.Data were analyzed using univariate, bivariate with chi-square test and multivariate with conditional logistic regression analysis. Results: From the results of multivariate analysis, four factors related to asphyxia were abnormal labor (OR=2.304;95%CI=1.402 to 3.787;p-value=0.001), premature rupture of membranes (OR=2.040;95%CI=1.019 to 4.083;p-value=0.044), anemia (OR=1.426;95%CI=1.182 to 1.720;p-value=0.000) and pregnancy spacing <2 years (OR=2.458;95%CI=1.060 to 5.698;p- value=0.036). Conclusion: Abnormal labor, premature rupture of membranes, anemia and pregnancy spacing <2 years were the risk factors of birth asphyxia in PKU Muhammadiyah Hospital, Bantul in 2014.